Optimal design of the volute for a turbocharger radial flow compressor. (May 2015) - Mojaddam, Mohammad; Hajilouy Benisi, Ali; Movahhedy, Mohammad Reza
In this research, design methods of radial flow compressor volutes are reviewed; the main criteria in volute primary designs are recognized and the most effective ones are selected. The effective parameters, i.e., spiral cross-section area, circumferential area distribution, exit cone, and tongue area of the compressor volute are parametrically studied to identify the optimum values. A numerical model has been prepared and verified through experimental data which are obtained from the designed turbocharger test rig. Different volutes are modeled and numerically evaluated using the same impeller and vane-less diffuser. For each model, the volute total pressure ratio, static pressure recovery and total pressure loss coefficients and the radial force on the impeller are calculated for different mass flow rates at design point and off-design conditions. The volute which shows better performance and causes lower the net radial force on the impeller at desired mass flow rates is selected as an optimal one. The results show the volute design approach differences at the design point and off-design conditions. Improving the pressure ratio and reducing total pressure loss at design point may result in the worse conditions at off-design conditions as well as increasing radial force on the impeller.